The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1029/2006jb004690
|View full text |Cite
|
Sign up to set email alerts
|

Crustal deformation in Kyushu derived from GEONET data

Abstract: An investigation was conducted on the horizontal crustal deformation in Kyushu using the coordinate data from GPS Earth Observation Network (GEONET) for the 4 years from 1998 to 2002, for which the annual variations are corrected. We examined the spatial differences in the displacement rate relative to the Amurian plate by subtracting the velocity of the Amurian plate at each of the Global Positioning System (GPS) stations. Models for interplate coupling in Hyuganada and the dilatational source beneath Sakuraj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Despite the simplicity, this model fits the observation very well, with an average error of approximately 1.0 mm/yr. A similar relation has been presented by Takayama and Yoshida (2007). Our model is an advanced version of their model with modifications of the fixed point and the optimum direction.…”
Section: Removing the Effects Of Tectonic Ground Deformation And The mentioning
confidence: 63%
See 1 more Smart Citation
“…Despite the simplicity, this model fits the observation very well, with an average error of approximately 1.0 mm/yr. A similar relation has been presented by Takayama and Yoshida (2007). Our model is an advanced version of their model with modifications of the fixed point and the optimum direction.…”
Section: Removing the Effects Of Tectonic Ground Deformation And The mentioning
confidence: 63%
“…Nishimura et al (2004) proposed that block rotation of the Ryukyu arc is the main factor. Takayama and Yoshida (2007) suggested that temporal variations in the inter-plate coupling affect the deformation rate. Wallace et al (2009) tried to explain the deformation field assuming an east-west striking shear zone in southern Kyushu.…”
Section: Removing the Effects Of Tectonic Ground Deformation And The mentioning
confidence: 99%
“…Kamata and Kodama (1999) suggested that this uplift started synchronously with counter-clockwise rotation of South Kyushu during the last 2 Myr and that these events were caused by a westward shift in the subduction direction of the PHS plate and associated trench retreat along the Ryukyu Trench. The contemporary geodetic velocity eld shows an eastward movement in southern Kyushu with respect to central Kyushu (Takayama and Yoshida, 2007), and the present-day crustal stress eld deduced from microearthquake focal mechanisms also reveals a change in the axis of minimum horizontal compressive stress from north-south to northeast-southwest in central Kyushu (Shimizu et al, 1993). The low-velocity zone beneath the Kyushu Mountains provides important insight into the tectonics of this region.…”
Section: Beneath the Kyushu Mountainsmentioning
confidence: 99%
“…Seno (1999) proposed that the stress eld represents viscous drag exerted by lateral mantle ow associated with upwelling in the East China Sea. In a more detailed regional study, Takayama and Yoshida (2007) umented a southward extensional displacement eld in and to the south of the Beppu-Shimabara Graben in western Kyushu and a southeastward extensional eld in southern Kyushu. They suggested, like Seno (1999), that southern Kyushu is being dragged at the base of the crust by ow in the mantle in response to both the uprising of hot material in the Okinawa Trough and retreat of the trench where the Philippine Sea plate subducts.…”
Section: Introductionmentioning
confidence: 99%
“…The north-south extensional tectonics is dominant in central Kyushu (Tada 1984;Takayama and Yoshida 2007). The Beppu-Shimabara rift zone (Matsumoto 1979), of which the south end is bounded by the Oita-Kumamoto tectonic line, is a subsidence zone due to the extension and may lead to the Okinawa trough (Tada 1984(Tada , 1985 ( Fig.…”
Section: Introductionmentioning
confidence: 99%